2021
DOI: 10.1016/j.scitotenv.2020.144133
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a continuous flow microbial fuel cell for treating synthetic swine wastewater containing antibiotics

Abstract: Microbial fuel cell (MFC) systems are promising technologies for wastewater treatment and renewable energy generation simultaneously. Performance of a double-chamber microbial fuel cell (MFC) to treat synthetic swine wastewater containing sulfonamide antibiotics (SMs) was evaluated in this study. The MFC was operated in continuous modes at different conditions. Results indicated that the current was successfully generated during the operation.The performance of MFC under the sequential anode-cathode operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The microorganisms of various genera in the Proteobacteria phylum play important roles in degrading substrates and generating electricity (Obata et al, 2020). Cheng et al (Cheng et al, 2021) noted that the high EAB abundances in both devices would have promoted COD removal, and the results confirmed that this did occurred. The three most common microbe phyla in the CW-MFC were Proteobacteria, Firmicutes, and Bacteroidetes.…”
Section: Analysis Of System Community Compositionmentioning
confidence: 85%
“…The microorganisms of various genera in the Proteobacteria phylum play important roles in degrading substrates and generating electricity (Obata et al, 2020). Cheng et al (Cheng et al, 2021) noted that the high EAB abundances in both devices would have promoted COD removal, and the results confirmed that this did occurred. The three most common microbe phyla in the CW-MFC were Proteobacteria, Firmicutes, and Bacteroidetes.…”
Section: Analysis Of System Community Compositionmentioning
confidence: 85%
“…The study by Apollon et al [16] has described that the MFC can generate green electrical energy through the metabolic reaction of an exoelectrogen. Conversely, 2 core problems still exist with the MFC such as the complete utilization of substrate by bacterial catalyst with results in unstable power generation, and low-power generation during the process [17][18][19]. Hence, it cannot be used on a larger scale like an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…MFCs makes up for the shortcomings of traditional biological treatment processes, and is an emerging innovative technology for sewage treatment and synchronous power generation (Liu and Yu, 2020;Raychaudhuri and Behera, 2022). In MFCs studies, domestic wastewater (Puig et al, 2011;James et al, 2020), industrial wastewater (Yu et al, 2015;Abbasi et al, 2016), and swine wastewater (Cheng et al, 2021) were demonstrated for power generation and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that MFCs has been successfully applied to remove ammonia nitrogen (NH 3 -N), biochemical oxygen demand (COD) and total phosphorus (TP) in aquaculture effluent, indicating that MFCs has great potential in the treatment of aquaculture effluent (Estrada-Arriaga et al, 2015;Cheng et al, 2021). Although MFCs has a good effect on the removal of COD from laboratory environmental wastewater, the removal of NH 3 -N and TP needs to be further improved (Estrada-Arriaga et al, 2015;Zhu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%